JAMINAN PEMELIHARAAN KESEHATAN BAGI MASYARAKAT MISKIN DI KOTA YOGYAKARTA - Eddy Kiswanto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2006)
The research aims to find out the implementation of JPKM before and after being organized by PT. Askes, the financing and health service accepted by those who join JPKM program in Yogyakarta City, and how useful was JPKM program according to poor citizens in Yogyakarta City. This research is designing to combine two methodologies, quantitative and qualitative method. A quantitative research needed to conduct a survey and a qualitative research aims to get more comprehensive view from stakeholders in the implementation of JPKM in Yogyakarta City. The results of this study are first, the low level of commitment from local government in Yogyakarta City in health sector. Second, Yogyakarta City has not yet developed its own social security system. Third, there is no complete database of poor citizens to be used in order to appoint the target for this health insurance program. Fourth, form the point of view of the target, health card has shown effective.